Cobitis nalbanti, a new species of spined loach from South Korea, and redescription of Cobitis lutheri (Teleostei: Cobitidae) - Vasil’eva, Ekaterina D.; Kim, Daemin; Vasil’ev, Victor P.; Ko, Myeong-Hun; Won, Yong-Jin (Zootaxa, 2016)
Cobitis nalbanti, new species, is described from the South Korean Han and Geum Rivers, draining to the Yellow Sea. It differs from its congeners by having a wide, ovoid lamina circularis; rounded scales with a large, slightly-displaced focal zone; a relatively long, protruded snout; the suborbital spine not reaching the center of the eye; the mandibular barbel not reaching the anterior edge of the eye; usually 12–14 dark brown blotches in the fourth Gambetta’s zone; a single elongated black spot on the upper part of the caudal-fin base; the only streak on the head running from the tip of the snout to the nape, across the eye; 2n=48–51 and NF=66. Cobitis nalbanti was previously identified as C. lutheri. Morphological analysis of C. lutheri shows that it is distinct in having a short obtuse snout, the suborbital spine reaching the center of the eye, the mandibular barbel reaching the anterior edge of the eye, usually less than 12 dark brown blotches in the fourth Gambetta’s zone, two spots at the caudal-fin base, several dark streaks on the head, and 2n=50, NF=70. A lectotype is selected for C. lutheri. Cobitis lutheri has a wide distribution in the Amur River basin, several rivers flowing into the Sea of Japan (East Sea), and in the northern part of Sakhalin Island.